Reasons of Weakeningh Pupils’ Learning Motivation: Attitude of Parents - Jegelevičienė, Violeta; Merfeldaitė, Odeta; Railienė, Asta (Pedagogika, 2016)
One of the major challenges faced by school pedagogues is to increase pupils’ motivation which affects the pupils’ attitude toward school, relations with teachers, learning time and efforts, involvement and participation in the education activities, academic achievements, behaviour and many other factors. According to the research, the pupil’s learning motivation and achievements are influenced by the parents’ engagement into the education process. However, in Lithuania there is still lack of continuous relationship between the school and family, including communication, cooperation and coordination. The aim of this article is to reveal the parents’ view on the involvement in the education process by promoting learning motivation of pupils. The article analyses how parents identify the phenomenon of weakening pupils’ learning motivation and what is the role of the class tutor in cooperating with parents while solving the learning motivation problem. The research was carried out in February–May 2015 and involved n = 418 parents of children studying in grades five and eight. The selection of parents was based on the probability sample: multistage sampling. In order to empirically justify the attitude of parents toward the reasons of pupils’ weakening learning motivation, it was necessary to identify the assumptions of their involvement in the solution of this problem. The inquiry was carried out only of parents of five and eight grade pupils of the large cities, therefore the conclusions shall not be applicable to the entire parents’ population. Pursuant to the research and according to the parents’ opinion the motivation of pupils’ learning is decreasing because of the curriculum and education process: the amount of learning load and organisation of the learning process. A very important factor of weakening learning motivation is a pupil himself/herself: his/her abilities and school attendance. Usually the parents treat weakening of learning motivation with learning achievements or with the information received from school. Involvement into the education process is usually promoted by the class tutor whose activities help parents identify the phenomenon of weakening pupils’ motivation to learn.